Ultimate Response of Strengthened RC Beams in the Flexural Using Plain Cementitious Composites Layer - Heniegal, Ashraf M.; Afefy, Hamdy M.; Baraghith, Ahmed T.; Eldwiny, Mostafa; Ibrahim, Omar Mohamed Omar (Manufacturing Technology Journal, 2024)
This paper aims to study the efficiency of using prefabricated layers made from plain cementitious composite materials for enhancing the flexural behavior of reinforced concrete (RC) continuous beams. The strengthening system was applied at 20 mm thickness, 150 mm width, and adequate development length. The prefabricated layers were placed in the tension cover in the positive and negative zones. All beams have the same geometric dimensions and positive and negative steel reinforcement ratios. The results showed that the prefabricated layer was deformed with the RC specimen without debonding, which enhanced the cracking patterns and distributed the crack width. A slight improvement in the strengthened beam capacity was 7% for the yielding load and 6% for the ultimate load. The energy absorption capacity of the strengthened beam decreased by 30.67%, whereas both beams achieved the same ductility index.
Keywords: Continuous beams; Prefabricated layers; Cementitious composite materials